PENGELOLAAN SARANA DAN PRASARANADI SEKOLAH DASAR NEGERI 1 DENA KECAMATAN MADAPANGGA - Nurwalidainismawati Nurwalidainismawati; Elsa Astuti; Eka Diniarti Putri; Kurniati Kurniati; Astria Ningsih; Putri Ramadhan (Pendikdas: Pendidikan Dasar, 2023)
The research objectives are (1) to describe the characteristics of the provision of facilities andinfrastructure; (2) distribution of facilities and infrastructure; and (3) maintenance of facilities and infrastructure. Qualitative research with ethnographic research design. Data collection techniques using observation, in-depth interviews, and documentation. Data analysis in this study used cross-site analysis for description. The results of the study are (1) Facilities and infrastructure are provided based on planning needs which is compiled together with the preparation of the school income and expenditure budget plan and is carried out in a school community meeting consisting of school principals, teachers, school committees, and school caretakers; (2) The distribution is carried out in two systems, namely the direct distribution of goods which are sent at once, the goods that have been received will be inventoried directly and distributed to school principals, teachers or caretakers who need them without going through the storage process first. Indirect distribution is carried out toÂ Facilities and infrastructure whose shipments are not completed all at once, so that before all shipments are complete, they cannot be handed over to those concerned; and (3) The maintenance of learning infrastructure is carried out by teachers and students by keeping the infrastructure clean. If damage occurs that cannot be repaired, the teacher reports it verbally to the school principal which is followed up with a written report to the school principal